The Mexico-Guatemala Border: New Controls on Transborder Migrations in View of Recent Integration Schemes? - Ángel Castillo, Manuel (Frontera Norte, 2017)
The Mexico-Guatemala border has historically been the site of many continuities and discontinuities: economic, demographic, environmental, cultural, ethnic, and political. However, recent transformations—due generally to political conflicts on both sides of the border— and economic integration—mostly trade-related—raise serious challenges to traditional mechanisms for the control and regulation of border dynamics. From a “national security” perspective, officials in both countries are calling for crime control in the area of drug, merchandise, and weapons trafficking. Most importantly, the Mexico-Guatemala border has confirmed its historical role as a place of intense population mobility, which requires appropriate regulation that will not impede the human or labor rights of migrants nor the well-being and sustainable development of the regions of origin and destination. Hence, governmental policies and international relations become focal points for discussion at both binational and multilateral levels. RESUMEN La frontera México-Guatemala ha sido históricamente un ámbito de continuidades y discontinuidades: económicas, demográficas, ambientales, culturales, étnicas y políticas. En la época actual, transformaciones recientes y procesos de integración económica plantean serios desafíos a los mecanismos tradicionales para el control y la regulación de la dinámica fronteriza. Pero más importante, la frontera México-Guatemala ha confirmado su papel histórico como un ámbito de intensa movilidad poblacional, la cual requiere una regulación apropiada que no atente contra los derechos humanos o –en su caso– laborales de los migrantes, ni tampoco contra el bienestar y el desarrollo sustentable de las regiones de origen y de destino de estas personas. Por lo tanto, las políticas gubernamentales y las relaciones internacionales se convierten en elementos críticos de discusión, tanto en el nivel binacional como multilateral.